Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Gender Terhadap Perilaku Keuangan pada Generation (Z) - Yulana, Desilfa; Suriyanti, Linda Hetri; Agustiawan (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to examine whether there is an influence of financial literacy, financial inclusion, and gender on financial behavior among Generation Z in the city of Pekanbaru. The data used in this study is primary data. This type of research is quantitative, with data collection methods using questionnaires, and the data obtained were processed using SPSS version 2.6. The population in this study encompasses workers and students of Generation Z in Pekanbaru City. The sample in this study consists of 81 respondents. Multiple regression analysis was used to test the hypothesis. The results of this study indicate that partially, financial literacy, financial inclusion, and gender have a significant effect on financial behavior among Generation Z in Pekanbaru.